Dizziness and Driving From a Patient Perspective - van Leeuwen, Roeland B.; Schermer, Tjard R.; Colijn, Carla; Bruintjes, Tjasse D. (Frontiers in Neurology, 2021)
Background: People with dizziness may experience driving-related limitations. Few data are available about the impact of dizziness on driving. Aim: The aim of this study is to investigate the impact of dizziness on driving, factors related to impairment (age, gender, and type of diagnosis), and the potential consequences for patients' ability to work. We also investigated whether the patients expected and actually received information about their dizziness-related fitness to drive from their physician. Methods: A cross-sectional, observational study was conducted in the Apeldoorn Dizziness Centre, a tertiary care referral centre for patients with dizziness. A consecutive cohort of patients was asked to complete a study-specific questionnaire about driving. Results: Between January 1, 2020, and December 20, 2020, 432 patients were included. Fifty-six percent of the patients in this group were female. The average age of patients was 58.3 years (SD 16). Overall, 191 of the 432 patients (44%) experienced limitations related to driving, and 40% of the patients who experienced limitations also experienced limitations to work related to their inability to drive. The subject of fitness to drive had not been discussed with their physician in 92% of the patients, and 24% of the whole patient group indicated that they would have liked to discuss this topic. The following factors, independently from each other, increased the chance of experiencing driving-related limitations: younger age, female sex, and the diagnosis of Meniere's disease. Conclusion: Dizzy patients, especially younger patients, women, and patients with Meniere's disease, regularly experience limitations related to driving, and this often means that they are unable to work. Driving is hardly ever discussed during a medical consultation. In our opinion, the topic of driving and dizziness should always be addressed during medical consultations in dizzy patients.